Level of Satisfaction of Admitted Patients - Abida Sultana , Bushra Anwar, Omera Naseer, Afifa Kulsoom (Journal of Rawalpindi Medical College, 2016)
Background: To determine the level of satisfaction of admitted patients in respect of three components of health services (doctors, nurses, facilities) in different wards and its comparison of level of satisfaction between male and female patients. Methods: In this cross sectional study admitted patients (n= 170) were surveyed using close-ended questionnaire. The variables noted were age, gender, type of room or ward, satisfaction with doctors, nurses and health facilities measured using different variables for each. Satisfaction level was graded as satisfied, no comments, not satisfied and was compared between male and female patients. Results: Out of 170 patients 82.53% were satisfied with health facilities. Most satisfying variables were attitude of doctors for which 91% were satisfied with it and timeliness of nurses as 90% patients were satisfied with it. Most unsatisfying variable was free medication availability as 61% were dissatisfied; followed by cleanliness with which 23% were dissatisfied; and thirdly, expertise of nurses, with it 17% were dissatisfied. Overall 15.84% patients were dissatisfied with health services. Conclusion: There was a reasonable degree of satisfaction in admitted patients of Holy Family Hospital with health services provided to them except for free medication and hygiene